INTEGRATING ISLAMIC CHARACTER EDUCATION AND PANCASILA VALUES: A CASE STUDY OF STIQ AS-SYIFA STUDENTS - Ismawati, Nova; Rustandi, Feri (STKIP Pesisir Selatan, 2025)
Strengthening Islamic character education through Pancasila values is a strategic priority in Islamic higher education (PTKIS), particularly at the As-Syifa Subang College of Al-Qur'anic Studies (STIQ). This study aims to examine three main aspects. First, the forms of character strengthening through Pancasila values manifested in curriculum integration, instilling values through campus activities such as community service, social service, and volunteer work, and the exemplary behavior of faculty members and leadership. Second, the factors influencing character development, including internal factors such as institutional vision, integrated curriculum, and educator capacity, as well as external factors such as national policies, social dynamics, and globalization trends. Third, the implications of character strengthening, both positive, such as increased religiosity, nationalism, and social tolerance, and negative, such as psychological pressure and the potential for exclusivism. The research used a qualitative approach with a case study method, involving 50 students as the main informants. Data were collected through semi-structured interviews, participatory observation, and documentary studies, then analyzed using the Miles and Huberman interactive model.